Portal web dinámico, para el desarrollo de habilidades y destrezas de los niños con síndrome de down en la unidad educativa especializada Cotopaxi en la parroquia Ignacio Flores - Analuisa Llano, Silvia Leonor (2016)
At the "Specialized Education Unit of Cotopaxi" from the Ignacio Flores Parish, Cotopaxi Province attends special children with Down syndrome, due to by its genetic disorder degree; they have problems in the teaching learning process about oral mode and cognitive skill. During these problems observation which have been presented, is done a technical analysis about children with those learning difficulties in their classroom work, so the investigators concluded for improving the students environment is satisfactory create a Dynamic Educative Portal web that allows child with a Down Syndrome encourage and manipulate information given at the web tools, because there are didactic games which permit them get information.